Analysis of Meteorological Trends of Yeldari Reservoir from Tropical Locality of Maharashtra State (India) to Evaluate Influence of changing Climate on Ichthyofauna Diversity - Shirale, Maroti Govindrao; Jagtap, Hanumant Shahaji (Asian Journal of Biological and Life Sciences)
Present investigation carried out to evaluate influence of changing climate with uneven meteorological trends to Ichthyofauna diversity of Yeldari reservoir of Parbhani district of Maharashtra for conservation purpose. Meteorological parameters like atmospheric temperature, humidity, evaporation and rainfall were studied for four consecutive years from 2016- 2019. During the investigation period of minimum atmospheric temperature (9.8°C) observed during December 2017 and maximum (42.5°C) observed May 2019. Lowest humidity (12%) observed during April 2017 and April 2019 while Highest humidity (88%) observed during September 2016, August 2018 and September 2019. Rate of evaporation observed minimum (2.8 mm) during September 2019 and maximum (16.6 mm) during May 2016. Annual rainfall was recorded as 926 mm in 2016, 735 mm in 2017, 744 mm in 2018 and 971 mm in 2019. In the investigation past and present meteorological trends are analysed to predict impacts on Ichthyofauna diversity of Yeldari reservoir. The results of investigation showed that, climate change and variation in meteorological parameters increased problems and threats to fish life.
Keywords: Climate change; Fish diversity; Meteorological parameters; Rainfall; Temperature; Yeldari reservoir